2020
DOI: 10.7150/jca.45678
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Thalidomide for Chemotherapy-induced Nausea and Vomiting

et al.

Abstract: Purpose: A substantial number of cancer patients discontinue chemotherapy due to severe chemotherapy-induced nausea and vomiting (CINV). This study aimed to evaluate the efficacy and safety of thalidomide (THD) in CINV. Methods: We searched different databases to identify related studies that investigated the efficacy and safety of THD in CINV. The primary outcomes were CINV in the acute (0-24 h), delayed (24-120 h), and overall (0-120 h) phases, respectively. The secondary outcomes were the safety of THD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Constipation caused by thalidomide can counteract the diarrhea from anti-cancer therapy, which is supported by previous clinical trials [25,26]. In addition, thalidomide can decrease nausea and vomiting induced by chemotherapy [32], which are also the common AEs of pyrotinib [14][15][16]. We believed that the use of thalidomide with synergistic antitumor effect and attenuation of gastrointestinal toxicity is a better option compared with prophylactic antidiarrheal drugs (such as loperamide) for patients treated with pyrotinib.…”
Section: Discussionmentioning
confidence: 70%
“…Constipation caused by thalidomide can counteract the diarrhea from anti-cancer therapy, which is supported by previous clinical trials [25,26]. In addition, thalidomide can decrease nausea and vomiting induced by chemotherapy [32], which are also the common AEs of pyrotinib [14][15][16]. We believed that the use of thalidomide with synergistic antitumor effect and attenuation of gastrointestinal toxicity is a better option compared with prophylactic antidiarrheal drugs (such as loperamide) for patients treated with pyrotinib.…”
Section: Discussionmentioning
confidence: 70%
“…They also found that thalidomide increased tumor perfusion and decreased vascular leakiness, which may enhance the delivery and efficacy of chemotherapy ( 12 ). Meta-analysis showed that thalidomide reduced nausea and vomiting in delayed and overall phases ( 16 ), increasing treatment tolerance for older patients. Whether thalidomide can enhance the anti-tumor effect of CDK4/6 inhibitors requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Thalidomide (THD), a derivative of glutamate, was originally used to treat nausea in pregnancy, later was banned because of its teratogenicity (14, 15). However, THD, as approved drugs, has been used in the treatment of a variety of solid tumors, with good efficacy and a certain degree of safety (16). At present, the effectiveness of THD in controlling CINV has become the focus of research.…”
Section: Introductionmentioning
confidence: 99%